GENETIC STRUCTURALISM IN THE SHORT STORY ANTHOLOGY "YANG LEBIH BIJAK DARIPADA PERI" BY RIZQI TURAMA - Wahid, Muhammad Aqil; Halimi, Halimi; Ghufron, Zaki (Annual International Conferences on Language, Literature, and Media, 2023)
Social realities such as repression and resistance have accompanied human civilization for hundreds of centuries. Repression and resistance exist as thesis and antithesis, shaping human civilization into what it is today. Repression is present in the form of enslaving fellow humans and interactions with the surrounding environment. In literature, these facts can be traced through genetic structuralism theory. The purpose of this research is to identify and describe repression, resistance, and ecological facts as a representation of societal reality or human facts in the short story anthology "Yang Lebih Bijak daripada Peri" and its impact on the social condition of society and to describe the relationship between human facts and the author's worldview perspective. This research uses a qualitative descriptive method with an analytical design. The data collection technique used is reading and note-taking. The data is analyzed through data reduction, data presentation, and concluding. The finding shows several forms of social realities that exist within the stories. These realities include capitalist and communal repression, resistance against the capitalist system and social contracts, and ecological facts such as environmental pollution and uncontrolled forest fires. These realities are representations of phenomena occurring within the author's worldview perspective.